2019
DOI: 10.1021/acssuschemeng.9b04931
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Biocatalytic Activity of l-Asparaginase Using Aqueous Solutions of Cholinium-Based Ionic Liquids

Abstract: l-Asparaginase (ASNase) is a high value enzyme for the pharmaceutical and food industries. Although ionic liquids (ILs) have been recognized as promising solvents or additives for biocatalysis, there are very few studies on the effect of ILs on the activation of ASNase. To address this, the enzymatic activity of a commercial ASNase in aqueous ILs was evaluated. ASNase was exposed for up to 24 h to aqueous solutions (0.001–0.050 mol·mol–1) of cholinium ([Ch])-based ILs, at three temperatures (25, 37, and 50 °C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…This agrees with previous reports on enzymatic activity in DES, as it has been shown that Lyz retains its activity when dissolved or surface-immobilised in DES. 19,42 Similarly, other enzymes were shown to remain functional in other choline-based neoteric solvents, such as L-asparaginase, 43 Lyz, 44 and lactate oxidase, 45 among others.…”
mentioning
confidence: 99%
“…This agrees with previous reports on enzymatic activity in DES, as it has been shown that Lyz retains its activity when dissolved or surface-immobilised in DES. 19,42 Similarly, other enzymes were shown to remain functional in other choline-based neoteric solvents, such as L-asparaginase, 43 Lyz, 44 and lactate oxidase, 45 among others.…”
mentioning
confidence: 99%
“…The enzymatic activity of HRP, AOC, and azurin was maintained in [Chn]­[DHP] and enhanced thermal stability of FDH was observed in [Chn]­[DHP] . The biocatalytic activity of l -asparaginase, a profitable enzyme for pharmaceutical and food industries, in aqueous solutions of Chn ILs was examined by Pereira and co-workers . It was evident that these ILs are efficient additives to increase the biocatalytic activity of l -asparaginase (up to 2-times) .…”
Section: Recent Advances In Exploring Cholinium-based Ionic Liquids F...mentioning
confidence: 99%
“…The biocatalytic activity of l -asparaginase, a profitable enzyme for pharmaceutical and food industries, in aqueous solutions of Chn ILs was examined by Pereira and co-workers . It was evident that these ILs are efficient additives to increase the biocatalytic activity of l -asparaginase (up to 2-times) . The effect of a series of Chn ILs on protease acitivity of APA was examined by Ricarte et al .…”
Section: Recent Advances In Exploring Cholinium-based Ionic Liquids F...mentioning
confidence: 99%
“…2c) [33]. Like other polymers and ionic compounds [16,33,34], Pluronic F68 and cholinium-based ILs can be thus used as ATPMS-forming components, not only because of ATPMS formation but also for their biocompatible/stabilization characteristics.…”
Section: Ccm Stability Studiesmentioning
confidence: 99%
“…Anyway, these CCM losses are far less intense than those due to pH and temperature increases, confirming the biocompatible character of cholinium ILs. Recently, Magri et al[33] demonstrated that cholinium ILs aqueous solutions maintain the enzymatic activity of Lasparaginase (ASNase). Similarly, [Ch]Cl and [Ch][Ac] have the most structural stabilizing aptitudes, while the increase of IL's anion alkyl chain length and temperature decreased the favorable stabilizing effects…”
mentioning
confidence: 99%